Understanding the circular economy: Overview of the issues - Gustavo Ferro (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2021)
This essay tries to synthesize a recent discussion on circular economics, aiming to clarify the concept, its relationship with the notion of "decoupling", and how technology, business, and economic policy influence it. In essence, circular economy means turning waste into something valuable. The concept encompasses some previous notions, such as bioeconomy. Technology of Fourth Industrial Revolution helps to decoupling growth from resource use. The reach of decoupling is disparate between growth optimistic and growth pessimistic thinkers. Business models comprehended in circular economy vary from eliminating waste, maximizing use extension of capital and durable consumption goods, until recovering materials and energy from process and products, turning goods into services by sharing, and replacing property by lease or pay-per-use models. Policies to induce or incentivize circular economy includes fiscal incentives through taxation and subsidization, command and control measures, and voluntary coordination efforts at the international level.
Keywords: Q20; Q50; 330; Circular economy; Fourth Industrial Revolution; Business; Public policy